2011
DOI: 10.1007/s13361-011-0198-5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Reactivity of theN-Acetyl-Cysteine Radical Cation and Anion: Does Radical Migration Occur?

Abstract: The structure and reactivity of the N-acetyl-cysteine radical cation and anion were studied using ion-molecule reactions, infrared multi-photon dissociation (IRMPD) spectroscopy, and density functional theory (DFT) calculations. The radical cation was generated by first nitrosylating the thiol of N-acetyl-cysteine followed by the homolytic cleavage of the S-NO bond in the gas phase. IRMPD spectroscopy coupled with DFT calculations revealed that for the radical cation the radical migrates from its initial posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 63 publications
0
53
3
Order By: Relevance
“…Nevertheless, gas-phase IR spectroscopy by Fornarini and co-workers revealed the long-lived distonic structure of the radical [28]. More recent work by Ryzhov and co-workers [27] suggests that radical migration to the α-carbon does occur. A comparison of the reactivity of the N-acetyl cysteine radical generated by in-source CID with that generated by ion trap-CID, together with IR spectroscopy of the species generated in source, suggested that within the timescale of the experiments~30 % conversion to the α-radical occurs.…”
Section: Ms3: Cid-ecd Of S-nitrosylated Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, gas-phase IR spectroscopy by Fornarini and co-workers revealed the long-lived distonic structure of the radical [28]. More recent work by Ryzhov and co-workers [27] suggests that radical migration to the α-carbon does occur. A comparison of the reactivity of the N-acetyl cysteine radical generated by in-source CID with that generated by ion trap-CID, together with IR spectroscopy of the species generated in source, suggested that within the timescale of the experiments~30 % conversion to the α-radical occurs.…”
Section: Ms3: Cid-ecd Of S-nitrosylated Peptidesmentioning
confidence: 99%
“…• NO neutral loss is observed following CID of Snitrosopeptides [5,22,[26][27][28], which might suggest a thermal process is occurring; however, no loss of + ions were observed when the energy of the electrons was reduced (Supplemental Figure 3).…”
Section: Electron Capture Dissociation Of S-nitrosylated Peptidesmentioning
confidence: 99%
“…This observation indicates hydrogen transfer from the first two amino acid residues to the thiyl radical. In fact, experimental and theoretical studies have shown that intramolecular hydrogen transfer to the thiyl radical is a facile process within polypeptides and cysteine ions [30][31][32][33]. [34] or CID of Nterminus amidated peptides [35].…”
Section: Formation Of C Z Ionsmentioning
confidence: 99%
“…Dissociation of the hydrogen rich radical cations often gives rise to c and z• ions, along with side-chain losses, through which they can convert quickly to hydrogen deficient radical ions [19][20][21]. Hydrogen deficient cations can be generated by a variety of methods: laser ablation followed by ultraviolet (UV) photoionization [22,23]; collision-induced dissociation (CID) of metal-ligand-peptide complexes [24][25][26]; CID of peptide derivatives with labile bonds such as S-nitrosylation [27,28], serine/homoserine nitrate esters [29], peroxycarbamates [30], 2,2,6,6-tetramethylpiperidine-1-oxy (TEMPO) [31,32], and 4,4'-azobis(4-cyanopentanoic acid) (Vazo 68) [33]; UV photolysis of iodinated tyrosine containing peptides [34]; or noncovalent complexes with photolabile precursor [35]; electroninduced dissociation of multiply charged ions [36,37]. Hydrogen deficient radical anions can be formed by electron detachment [38] or photodetachment [39] from multiply deprotonated molecules, CID of peptide-metal complexes [40,41], and photodissociation of iodinated peptide [42].…”
mentioning
confidence: 99%
“…Several groups have utilized both experimental approaches (i.e., ion/molecule reactions [14,15,27] and ion spectroscopy [43][44][45]) and theoretical calculations [21,[46][47][48][49] to investigate the structures of amino acid or small peptide radical ions. Radical ion chemistry, such as intramolecular radical migration [27,50] and competition between charge-and radical-directed dissociation upon collisional activation [49][50][51] have also been explored with different chemical systems. The capability of controlling the radical site upon its formation is highly desirable in studying the fundamental aspects as mentioned above.…”
mentioning
confidence: 99%